Interaction of 12C ions with the mouse retinal response to light. (26th June 2015) - Carozzo, Simone; Ball, Sherry L.; Narici, Livio; Schardt, Dieter; Sannita, Walter G.
Highlights: Astronauts report phosphenes possibly caused by heavy radiation. The mouse retina was stimulated by light or light + 12 C ions in particle accelerator. 12 C accelerated ions appear to compete with light at photoreceptor level. 12 C ions enhance the retinal oscillatory and the cortical responses to light. A manifold effect of heavy ions on the retina may result in malfunctioning in space. Abstract: Astronauts in orbit reported phosphenes varying in shape and orientation across the visual field; incidence was correlated with the radiation flux. Patients with skull tumors treated by 12 C ions and volunteers whose posterior portion of the eye was exposed to highly ionizing particles in early studies reported comparable percepts. An origin in radiation activating the visual system is suggested. Bursts (∼4 ms) of 12 C ions evoked electrophysiological mass responses comparable to those to light in the retina of anesthetized wild-type mice at threshold flux intensities consistent with the incidence observed in humans. The retinal response amplitude increased in mice with ion intensity to a maximum at ∼2000 ions/burst, to decline at higher intensities; the inverted-U relationship suggests complex effects on retinal structures. Here, we show that bursts of 12 C ions presented simultaneously to white light stimuli reduced the presynaptic mass response to light in the mouse retina, while increasing the postsynaptic retinal and cortical responses amplitude and the phase-locking to stimulus of cortical low frequency and gamma (∼25–45 Hz) responses. These findings suggest 12 C ions to interfere with, rather than mimicking the light action on photoreceptors; a parallel action on other retinal structures/mechanisms resulting in cortical activation is conceivable. Electrophysiological visual testing appears applicable to monitor the radiation effects and in designing countermeasures to prevent functional visual impairment during operations in space.